Avaliação da contagem plaquetária pelo contador automático QBC Vet Autoread comparado com estimativa em esfregaço sanguíneo e contagem em hemocitômetro - Schweirgert, Augusto [UNESP]; Rezende, Fabio Hosoi; Fantoni, Denise Tabacchi; Moroz, Ludmila Rodrigues (Univ Estadual Londrina, 2010)
The platelet blood count in laboratorial routine provides to the clinician important information about the hemostasis of the patient. There are many techniques described, however the gold standard techniques realized in hemocytometer spent a lot of time, making this technique impracticable in great routines. This research had the intent to evaluate if the automatic veterinary blood counter QBC Vet Autoread (R), whose results get five minutes to be ready, is capable to offer a trustworthy platelet count number. To this end, were evaluated the correlations among three different forms of platelets count in dogs: count in automatic blood counter QBC Vet Autoread (R), estimative in blood smear and the gold standard method by manual count in hemocytometer. The viability and confidence use of automatic blood counters of the medicine veterinary routine. Seventeen dogs were chosen randomly way, in the medical and surgical routine of HOVET-USP. The analysis revel high correlation between the hemocytometer and the estimative in blood smear (r=0,875) and between the hemocytometer and automatic blood count by QBC Vet Autoread (R) (r=0,939). Conclude that the platelet blood cont by QBC Vet Autoread (R), in addition to be fast, it's more truthful when compared with estimative in blood smear, although the latter one also had elevated correlation. However, morphological analysis through the smears cannot be dismissed because none of the other two techniques evaluated have the ability to assess platelet morphological changes.
Evaluation of platelet count by automatic blood counter QBC Vet Autoread (R) compared with blood smear estimative and count by hemocytometer
Keywords: Count of platelets; canine; hemocytometer; blood smear estimative; QBC Vet Autoread (R)